A New Method for FMR1 Gene Methylation Screening by Multiplex Methylation-Specific Real-Time Polymerase Chain Reaction - Marjanu Hikmah Binti Elias; Ravindran Ankathil; Abdul Razak Salmi; Wanna Sudhikaran; Pornprot Limprasert; Alwi Zilfalil (Mary Ann Liebert, Inc., 2024)
Fragile X Syndrome (FXS) is the most common form of inherited mental retardation in men. It is caused by abnormalities in the FMR1 gene that are associated with CGG repeat expansion and the hypermethylation status of its promoter. Methylated alleles lead to transcriptional inhibition and consequent loss of Fragile X Mental Retardation Protein. Chemical modification of cytosine to uracil by bisulfite treatment has proved to be an attractive method for DNA methylation studies that precludes labor-intensive Southern blot analysis, which is the gold standard test for FXS. In this report, bisulfite-treated DNA samples were amplified using real-time multiplex methylation-specific polymerase chain reaction followed by melting curve analysis. Our results show that all control samples with known CGG repeat numbers and methylation statuses were correctly diagnosed. The samples from 43 male patients were also successfully diagnosed, which were in complete agreement with the results of Southern blotting. By such means, 39 patients were found to have an unmethylated allele; 3, a fully mutated allele; and 1, both methylated and unmethylated alleles, thus implying a diagnosis of mosaicism. In conclusion, we find our method to be convenient for screening a large number of male patients with FXS, because it is rapid and easy to perform, especially when there is a low quantity of DNA that must be sensitively and accurately assayed.